The doubt of the apostles and the resurrection faith of the Early Church the post-resurrection appearance stories of the Gospels in ancient reception and modern debate - Atkins, J. D., 1976- (Wissenschaftliche Untersuchungen zum Neuen Testament., 2019)
"Why do the Gospels depict the risen Jesus as touchable and able to eat? J.D. Atkins challenges the common view that Luke 24 and John 20 are apologetic responses to docetism by re-examining the redaction of the appearance stories in light of their reception among early docetists and church fathers."--Page 4 of cover